MENINGKATKAN BERAT VOLUME KERING TANAH VERMICULITE MENGGUNAKAN SERBUK MARMER - Hadi Santoso; Yosef Cahyo; Ahmad Ridwan (Jurnal Manajemen Teknologi & Teknik Sipil, 2020)
Clay soil is soil that has mineral particles that produce plastic properties in the soil when mixed with water. Clay soils can be distinguished according to their constituent minerals. Vermiculite is one of the clay minerals that is often found in clay soils and has almost the same properties as montmorillonite, namely it absorbs a lot of water which will fill the pore cavities so that the soil will expand and consequently its strength will decrease. The method of soil stability in the following research is to use marble powder waste at variations of the addition of 0%, 6%, 12% and 18% on Vermiculite soil. In the soil stability test, the specimens were mixed with Vermiculite soil with marble powder by testing the Fill Weight, Consistency Limit (Atterberg Limit) and Soil Compaction (Proctor). In the results of the study the original soil structure was categorized as Vermiculite and after adding marble powder to the addition of a maximum variation of 12%, the Liquid Limit value increased to 56% and the Plastic Limit value increased to 24.49%, so that the plastic index could increase to 31.64 %. During the compaction test with the condition of the specimen being perfectly solid, the dry volume weight of the original soil was 1.508 gr/cm3 and after adding 12% marble powder waste, the dry volume weight increased to 1,569 gr/cm3.Â Tanah lempung adalah tanah yang memiliki partikel-partikel mineral yang menghasilkan sifat-sifat plastis pada tanah bila dicampur dengan air. Tanah lempung dapat dibedakan menurut mineral penyusunnya. Vermiculite merupakan salah satu mineral lempung yang sering dijumpai pada tanah lempung dan mempunyai sifat hampir sama dengan montmorilonite yaitu banyak menyerap air yang akan mengisi rongga pori sehingga tanah akan mengembang dan beraktibat kekuatannya menurun. Cara stabilitas tanah pada penelitian berikut adalah dengan menggunakan limbah serbuk marmer pada variasi penambahan 0%, 6%, 12% dan 18% pada tanah Vermiculite. Pada test uji stabilitas tanah adalah dengan menggunakan benda uji mix tanah Vermiculite dengan serbuk marmer dengan melakukan uji Berat Isi, Batas konsistensi (Atterberg Limit) dan Pemadatan Tanah (Proctor). Pada hasil penelitian struktur tanah asli dikategorikan Vermiculite dan setelah ditambah serbuk marmer pada penambahan divariasi maksimal sebesar 12%, nilai Liquid Limit naik menjadi 56% dan nilai Plastic Limit mengalami kenaikan menjadi 24,49%, sehingga index plastic dapat mengalami peningkatan menjadi 31,64%. Saat uji pemadatan dengan kondisi benda uji padat sempurna, berat volume kering tanah asli sebesar 1,508 gr/cm3 dan setelah ditambahkan limbah serbuk marmer sebesar 12% mengalami peningkatan berat volume kering menjadi 1,569 gr/cm3